Genomic and Gene-Level Distribution of Histone H3 Dimethyl Lysine-27 (H3K27me2) in Arabidopsis - Park, Sunchung (Public Library of Science, 2012)
Histone lysine methylation patterns underlie much of the functional diversity of nucleosomes in eukaryotes, and an interesting aspect of histone methylation is the potential functional specificity for different methylation states on a given lysine. Trimethylation of histone H3 (H3K27me3) is intimately related to developmental gene silencing through the so-called Polycomb Group (PcG) mechanism. How this modification becomes established at PcG-repressed loci is generally not known, but it has been suggested that it may be facilitated by prior occupancy by H3K27me2. In this study we mapped the genomic and gene-level distribution of H3K27me2 in Arabidopsis thaliana using ChIP and a high-density tiling microarray, and integrated this with previous maps of other chromatin features and gene expression data. At the genome level, H3K27me2 enrichment sites were sparsely distributed across chromosomes, within an average size expected for a single nucleosome, and contrasted with the longer domains seen for H3K27me3. In both heterochromatic and euchromatic segments of the genome, H3K27me2 enrichment was often localized within transposon-related genes, with the longest genomic stretches of this modification corresponding to retroelements. However, H3K27me2 was more frequently found within protein-coding genes. These genes generally also showed moderate enrichment for H3K27me3, but H3K27me2 was strongly depleted within those genes most enriched in H3K27me3. H3K27me2 within highly transcribed genes was at highest levels at transcriptional starts and was strongly depleted throughout the transcribed regions, and reached higher levels at active than at silent promoters.